A randomized controlled trial of the effectiveness of Housing First in a small Canadian City - Aubry, Tim; Bourque, Jimmy; Goering, Paula; Crouse, Susan; Veldhuizen, Scott; LeBlanc, Stefanie; Cherner, Rebecca; Bourque, Paul-Émile; Pakzad, Sarah; Bradshaw, Claudette (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background The paper presents two-year findings from a study investigating the effectiveness of Housing First (HF) with assertive community treatment (ACT) in helping individuals with serious mental illness, who are homeless or precariously housed and living in a small city, to become stably housed. Methods The research design was a parallel group non-blinded RCT with participants randomly assigned after the baseline interview to receive HF with ACT (N = 100) or treatment as usual (TAU; N = 101). Participants were interviewed every 3 months over 21/24 months to investigate changes on a range of housing and psychosocial outcomes. The primary outcomes were housing stability (as defined by a joint function of number of days housed and number of moves) and improvement in community functioning. Secondary predicted outcomes were improvements in self-rated physical and mental health status, substance use problems, quality of life, community integration, and recovery. Results An intent-to-treat analysis was conducted. Compared to TAU participants, HF participants who entered housing did so more quickly (23.30 versus 88.25 days, d = 1.02, 95% CI [0.50–1.53], p < 0.001), spent a greater proportion of time stably housed (Z = 5.30, p < 0.001, OR = 3.12, 95% CI [1.96–4.27]), and rated the quality of their housing more positively (Z = 4.59, p < 0.001, d = 0.43, 95% CI [0.25–0.62]). HF participants were also more likely to be housed continually in the final 6 months (i.e., 79.57% vs. 55.47%), χ2 (2, n = 170) = 11.46, p = .003, Cramer’s V = 0.26, 95% CI [0.14–0.42]). HF participants showed greater gains in quality of life, (Z = 3.83, p < 0.001, ASMD = 0.50, 95% CI [0.24–0.75]), psychological integration (Z = 12.89, p < 0.001, pooled ASMD = 0.91, 95% CI [0.77–1.05]), and perceived recovery (Z = 2.26, p = 0.03, ASMD = 0.39, 95% CI [0.05–0.74]) than TAU participants. Conclusions The study indicates that HF ends homelessness significantly more rapidly than TAU for a majority of individuals with serious mental illness who have a history of homelessness and live in a small city. In addition, compared to TAU, HF produces psychosocial benefits for its recipients that include an enhanced quality of life, a greater sense of belonging in the community, and greater improvements in perceived recovery from mental illness. Trial registration International Standard Randomized Control Trial Number Register Identifier: ISRCTN42520374 , assigned August 18, 2009.